Direct democracy and subjective regime legitimacy in Europe. Issue 4 (7th June 2017) - Gherghina, Sergiu
ABSTRACT: While much research focuses on the causes and consequences of direct democracy and regime legitimacy, little attention has been paid to the potential relationship between them. In an attempt to fill this void, this paper focuses on the legal provisions for direct democracy and its use. The key argument is that possibilities for the public's direct involvement reflect high importance given to citizens, openness of the regime towards different modes of decision-making, and ways to avoid unpopular institutions. Consequently, citizens are likely to accept and support the regime, improving or maintaining its legitimacy. The cross-national analysis includes 38 European countries ranging from transition countries to established democracies. It uses bivariate statistical analysis and country-level data collected from legislation, secondary sources, and aggregate surveys.